Tính
G=\(\sqrt{18,5-6\sqrt{3}}-\sqrt{18,5+6\sqrt{3}}\)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
g: \(=\left|\sqrt{6}-1\right|=\sqrt{6}-1\)
h: \(=\left|2\sqrt{3}-1\right|=2\sqrt{3}-1\)
l: \(=\left|2-\sqrt{3}\right|-2=2-\sqrt{3}-2=-\sqrt{3}\)
j: \(=\left|3-\sqrt{6}\right|+\left|2\sqrt{6}-3\right|\)
\(=3-\sqrt{6}+2\sqrt{6}-3=\sqrt{6}\)
\(E=(\sqrt{18}-3\sqrt{6}+\sqrt{2}).\sqrt{2}+6\sqrt{3} \\ = (3\sqrt{2}-3\sqrt{6}+\sqrt{2}).\sqrt{2} + 6\sqrt{3} \\ = 6 - 6\sqrt{3}+2 + 6\sqrt{3} \\ = 8\)
\(G=(2\sqrt2-\sqrt5+\sqrt{18}).(\sqrt{50}+\sqrt5) \\ =(2\sqrt2-\sqrt5+3\sqrt2).\sqrt5(\sqrt{10}+1) \\ = (5\sqrt2-\sqrt5). \sqrt5 (\sqrt{10}+1) \\ = (5\sqrt{10}-5)(\sqrt{10}+1) \\ = 5(\sqrt{10}-1)(\sqrt{10}+1)=5.9=45\)
a: \(=\left(\dfrac{\sqrt{6}\left(\sqrt{2}-1\right)}{2\left(\sqrt{2}-1\right)}+1\right)\cdot\dfrac{1}{2+\sqrt{6}}\)
\(=\left(\dfrac{\sqrt{6}}{2}+1\right)\cdot\dfrac{1}{\sqrt{6}+2}=\dfrac{\sqrt{6}+2}{2\left(\sqrt{6}+2\right)}=\dfrac{1}{2}\)
b: \(=3\sqrt{3}-\dfrac{6}{\sqrt{3}}+1-\sqrt{3}\)
\(=2\sqrt{3}-2\sqrt{3}+1=1\)
a) Ta có: \(A=\sqrt{\sqrt{3}+\sqrt{2}}\cdot\sqrt{\sqrt{3}-\sqrt{2}}\)
\(=\sqrt{\left(\sqrt{3}+\sqrt{2}\right)\left(\sqrt{3}-\sqrt{2}\right)}\)
\(=\sqrt{3-2}=1\)
b) Ta có: \(B=\sqrt{5-2\sqrt{6}}+\sqrt{5+2\sqrt{6}}\)
\(=\sqrt{\left(\sqrt{3}-\sqrt{2}\right)^2}+\sqrt{\left(\sqrt{3}+\sqrt{2}\right)^2}\)
\(=\sqrt{3}-\sqrt{2}+\sqrt{3}+\sqrt{2}\)
\(=2\sqrt{3}\)
`A=sqrt{sqrt3+sqrt2}.sqrt{sqrt3-sqrt2}`
`=sqrt{(sqrt3+sqrt2)(sqrt3-sqrt2)}`
`=sqrt{3-2}=1`
`b)B=sqrt{5-2sqrt6}+sqrt{5+2sqrt6}`
`=sqrt{3-2sqrt6+2}+sqrt{3+2sqrt6+2}`
`=sqrt{(sqrt3-sqrt2)^2}+sqrt{(sqrt3+sqrt2)^2}`
`=sqrt3-sqrt2+sqrt3+sqrt2=2sqrt3`
`c)C=3-sqrt{3-sqrt5}`
`=3-sqrt{(6-2sqrt5)/2}`
`=3-sqrt{(sqrt5-1)^2/2}`
`=3-(sqrt5-1)/sqrt2`
`=3-(sqrt{10}-sqrt2)/2`
`=(6-sqrt{10}+sqrt2)/2`
a) \(\dfrac{3}{2}\sqrt{6}+2\sqrt{\dfrac{2}{3}}-4\sqrt{\dfrac{3}{2}}-\dfrac{6}{\sqrt{6}}=\dfrac{3}{2}\sqrt{6}+\dfrac{2}{3}\sqrt{6}-2\sqrt{6}-\dfrac{6}{\sqrt{6}}\)
\(=\dfrac{1}{6\sqrt{6}}-\dfrac{6}{\sqrt{6}}=-\dfrac{35}{6\sqrt{6}}\)
b)\(\left(\sqrt{6}+\sqrt{5}\right)^2+\left(\sqrt{6}-\sqrt{5}\right)^2\)
\(=6+2\sqrt{30}+5+6-2\sqrt{30}+5=22\)
\(G=0\)
\(Ok\)
\(G^2=18,5-6\sqrt{3}+18,5+6\sqrt{3}-2\sqrt{\left(18,5-6\sqrt{3}\right)\left(18,5+6\sqrt{3}\right)}\)
\(=37-2.\sqrt{18,5^2-\left(6\sqrt{3}\right)^2}\)
\(=37-2.\sqrt{\frac{937}{4}}=37-2.\frac{\sqrt{937}}{2}\)
\(=37-\sqrt{937}\)\(\Rightarrow G=\sqrt{37-\sqrt{937}}\)